2020
DOI: 10.1142/s0129065720500513
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Reorganization of the Cortical Functional Brain Network in Affective Processing and Cognitive Reappraisal

Abstract: Emotion and affect play crucial roles in human life that can be disrupted by diseases. Functional brain networks need to dynamically reorganize within short time periods in order to efficiently process and respond to affective stimuli. Documenting these large-scale spatiotemporal dynamics on the same timescale they arise, however, presents a large technical challenge. In this study, the dynamic reorganization of the cortical functional brain network during an affective processing and emotion regulation task is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…This type of analyses failed to take advantage of the region-specific neuronal information, or the spatiotemporal-varying interactions at the network level (e.g., cluster, time-varying pattern) to allow a deeper understanding of the brain-emotion relationship. As indicated in a previous study, emotion processing and regulation is likely to involve complex neural circuits in a time-varying manner rather than any independent brain region ( Mauss and Robinson, 2009 ; Fang et al, 2020 ). Besides, various studies have reported that the frontal cortex seems to play a more essential role in emotion-related activity compared to other brain regions such as temporal, parietal, and occipital ( Sarno et al, 2016 ).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…This type of analyses failed to take advantage of the region-specific neuronal information, or the spatiotemporal-varying interactions at the network level (e.g., cluster, time-varying pattern) to allow a deeper understanding of the brain-emotion relationship. As indicated in a previous study, emotion processing and regulation is likely to involve complex neural circuits in a time-varying manner rather than any independent brain region ( Mauss and Robinson, 2009 ; Fang et al, 2020 ). Besides, various studies have reported that the frontal cortex seems to play a more essential role in emotion-related activity compared to other brain regions such as temporal, parietal, and occipital ( Sarno et al, 2016 ).…”
Section: Introductionmentioning
confidence: 75%
“…In this context, it has been showed that increased theta power in parietal area is linked to high arousal ( Aftanas et al, 2002 ). Previous studies also suggested that brain-emotion relationship could be characterized by complex network interactions with more fine-grained spatiotemporal resolution ( Nguyen et al, 2019 ; Fang et al, 2020 ). In sum, the optimal measurement protocol for EEG-based emotion studies remains to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various approaches have been proposed to capture the fluctuations in brain activity, the utilization of temporal networks to quantify these fluctuations is only beginning to be studied [25]. Through adding time-varying aspects of FC to static network, the temporal network models could help reveal the dynamic variations of functional coordination between different functional units [26], and thus the changes in network topologies could be investigated on a fine time scale [25]. Most recently, Thompson et al, [27] introduced a temporal network analysis framework and verified the usefulness using resting-state fMRI data.…”
Section: Introductionmentioning
confidence: 99%
“…The DLPFC serves multiple crucial functions whilst being richly functionally connected. It is not surprising that this region is widely acknowledged as playing a key role in reappraisal 26 . However, the evidence to support this claim is mostly correlational and hardly provides direct causal support.…”
Section: Introductionmentioning
confidence: 99%